Two new species of Hyalella Smith, 1874 (Malacostraca: Amphipoda: Hyalellidae) from the state of Santa Catarina, Brazil - Reis, Giovanna De Oliveira; Bueno, Alessandra Angélica De Pádua; Araujo, Paula Beatriz (Zootaxa, 2023)
The genus Hyalella Smith, 1874 occurs exclusively in the Americas. In Brazil, the states of Santa Catarina and Rio Grande do Sul have the largest number of records with 20 species. This paper presents two new species for the state of Santa Catarina, Brazil. The serrate setae with accessory seta, a new type of seta, is registered for the genus and observed on gnathopods 1 and 2. Additionally, microtrichs are reported on articles, a detail that has not been mentioned in previous studies. Hyalella carsone sp. nov. is characterized by gnathopod 1 with comb-scales from the basis to the carpus, gnathopod 2 dactylus with proximal margin strongly serrated and the presence of serrate setae on the articles of gnathopods 1 and 2. Hyalella wangarie sp. nov. is characterized by gnathopod 2 palm not sinuous with margin inconspicuously serrated, peduncle and inner ramus of the pleopod with simple setae, presence of curved seta on uropod 1 of male and gnathopod 1 palm on female slightly serrated. In this work we expand the number of species from Brazil and increase the morphological knowledge of the genus Hyalella.